Synthesis, Characterization, Thermal, NLO and Quantum-Chemical Studies on N-Acetyl-2,6-bis(4-methoxyphenyl)-3-ethylpiperidin-4-one - V. Mohanraj, V. X; Ponnuswamy, S.; Muthuraja, P.; Dhandapani, M. (Asian Journal of Chemistry, 2020)
Growth of a new organic single crystal of N-acetyl-2,6-bis(4-methoxyphenyl)piperidin-4-one (APM3EPO) is reported by using a slow evaporation method. The characterization of the crystal was done by IR and NMR spectra. Further, electronic spectrum and TG/DTA studies have also been carried out. The SHG efficiency of the crystal was found to be closer to that of standard KDP (potassium dihydrogen orthophosphate) using the modified Kurtz-Perry powder test employing Nd: YAG laser as the source of IR radiation. The calculated hyperpolarizability values were also projected to confirm the aptness of the crystal for non-linear optical applications. Optimization of the molecular structure of APM3EPO is done at the basic level of B3LYP/6-311(d,p) and the corresponding molecular properties such as HOMO-LOMO and Mulliken charge analyses are carried out at the same level of theory.